1997
DOI: 10.1074/jbc.272.22.14489
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Mitogen-activated Protein Kinase Kinase 4 (MKK4)/c-Jun NH2-terminal kinase 1 and MKK3/p38 Pathways Regulated by MEK Kinases 2 and 3

Abstract: We previously reported the isolation of cDNAs encoding two mammalian mitogen-activated protein kinase (MAPK)/extracellular-regulated kinase (ERK) kinase kinases, designated MEKK2 and MEKK3 (Blank, J.L., Gerwins, P., Elliott, E.M., Sather, S. These data indicate that MKK3 is preferentially activated by MEKK3, whereas MKK4 is activated both by MEKK2 and MEKK3. Consistent with these observations, MEKK2 and MEKK3 also activated JNK1 in vivo. However, MEKK3 failed to activate p38 when coexpressed in either the abse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
88
1
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(96 citation statements)
references
References 76 publications
(134 reference statements)
6
88
1
1
Order By: Relevance
“…MAP(3)Ks participate in the early steps of a signal transduction pathway that will promote various cellular processes in responses to a number of external stimuli through a sequential MAP(3)K > MAP(2)K > MAPK phosphorylation cascade (Chang and Karin 2001;Pearson et al 2001). In accordance to this general scheme, MEKK3 is known to phosphorylate a number of MAP(2)K (MEK/MKK1-7), which leads to the activation of their specific downstream MAPK (ERK1/2, JNK/SAPK, ERK5, and p38) (Blank et al 1996;Deacon and Blank 1997;Ellinger-Ziegelbauer et al 1997;Chao et al 1999;Deacon and Blank 1999;Uhlik et al 2003). MEKK3 is also involved in the NF-κB pathway where it activates the IKK complex in response to TNFα and LPS (Yang et al 2001;Schmidt et al 2003;Samanta et al 2004).…”
Section: Map3k3 (Mekk3)mentioning
confidence: 99%
“…MAP(3)Ks participate in the early steps of a signal transduction pathway that will promote various cellular processes in responses to a number of external stimuli through a sequential MAP(3)K > MAP(2)K > MAPK phosphorylation cascade (Chang and Karin 2001;Pearson et al 2001). In accordance to this general scheme, MEKK3 is known to phosphorylate a number of MAP(2)K (MEK/MKK1-7), which leads to the activation of their specific downstream MAPK (ERK1/2, JNK/SAPK, ERK5, and p38) (Blank et al 1996;Deacon and Blank 1997;Ellinger-Ziegelbauer et al 1997;Chao et al 1999;Deacon and Blank 1999;Uhlik et al 2003). MEKK3 is also involved in the NF-κB pathway where it activates the IKK complex in response to TNFα and LPS (Yang et al 2001;Schmidt et al 2003;Samanta et al 2004).…”
Section: Map3k3 (Mekk3)mentioning
confidence: 99%
“…4) (Deacon and Blank, 1997;Uhlik et al, 2003;Fritz et al, 2006). More recent evidence suggests that it also regulates activities of ERK5 (Chao et al, 1999) and the transcription factor, NF B (Zhao and Lee, 1999;Yang et al, 2001).…”
Section: Mekk3 (Omim#*602539)mentioning
confidence: 99%
“…As shown in Fig. 4D, increasing (31), we determined whether this autophosphorylation could be increased in the presence of reduced Trx. It is plausible that Trx might directly reduce the Cys-246 and Cys-266 due to its thiol-reducing activity, and it could thus induce autophosphorylation of MKK4 on Thr-261 or Ser-257.…”
Section: Cys-246 and Cys-266 In Mkk4 Are Specific Targets Of Trx And mentioning
confidence: 99%
“…Trx Directly Activates MKK4 without the Involvement of MEKK1 in ECs-MEKK1 is an upstream kinase that phosphorylates MKK4/MKK7 leading to their activation (31). Studies have shown that Cys-1238 in MEKK1 is redox-sensitive, and the glutathionylation of this residue inhibits MEKK1 activation (36).…”
Section: Inhibition Of Jnk Potentiates Mnsod Induction By Trx Inmentioning
confidence: 99%